2021
DOI: 10.1177/02724316211036744
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Life Events Spill-Over on Family Functioning and Adolescent Adjustment

Abstract: We examined US parent and youth perceptions of how life events, both positive and negative, associated with COVID-19 resulted in changes in family and youth functioning. Families ( n = 105, 80% white, 48% male, and 87% mothers) completed surveys during the pandemic (May to July 2020) and 3 years prior (for youth ages M = 10.6, SD = 1.17 and M = 13.6, SD = 1.19). Declines in youth, though not parent, report of open family communication, parental support, and family satisfaction were found. Declines were associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
37
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 49 publications
6
37
0
2
Order By: Relevance
“…This was also reported in the study by Hussong et al (2021), who found that family functioning typically stays intact, even during pandemic circumstances. The study by Hussong et al (2021) also found that higher socioeconomic status (SES) acted as a protective factor against isolation stress and promoted greater levels of positive events during the COVID-19 pandemic, which positively influenced family functioning. Given that our sample of families was biased toward a high SES, this may explain why most of the families reported healthy functioning during the pandemic.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…This was also reported in the study by Hussong et al (2021), who found that family functioning typically stays intact, even during pandemic circumstances. The study by Hussong et al (2021) also found that higher socioeconomic status (SES) acted as a protective factor against isolation stress and promoted greater levels of positive events during the COVID-19 pandemic, which positively influenced family functioning. Given that our sample of families was biased toward a high SES, this may explain why most of the families reported healthy functioning during the pandemic.…”
Section: Discussionsupporting
confidence: 80%
“…Approximately 75% of the sample had a score below 2 points, indicating a low prevalence of unhealthy family functioning, even during the COVID-19 pandemic. This was also reported in the study by Hussong et al (2021), who found that family functioning typically stays intact, even during pandemic circumstances. The study by Hussong et al (2021) also found that higher socioeconomic status (SES) acted as a protective factor against isolation stress and promoted greater levels of positive events during the COVID-19 pandemic, which positively influenced family functioning.…”
Section: Discussionsupporting
confidence: 80%
“…Studies on how COVID‐19 impacts on family functioning have generated inconsistent results with some concluding deterioration (Feinberg et al, 2021; Hussong et al, 2020) and others reporting well functioning (Fernandes et al, 2020; López et al, 2020). Among Chinese populations, studies on family process during COVID‐19 are limited.…”
Section: Introductionmentioning
confidence: 99%
“…The restrictive measures put in place to stem the diffusion of the COVID-19 virus have implied an important impact on families’ everyday functioning [ 1 , 2 , 3 ]. Nevertheless, some families have shown adaptive responses to the adverse circumstances imposed by the COVID-19 preventive strategies [ 13 ], maintaining a positive involvement with family members and the extra-family social network [ 14 , 15 ], and experiencing a sense of self-efficacy [ 2 ]. Nevertheless, national and international research reported that a large part of families of the general population experienced the pandemic as a traumatic event, manifesting anxiety, depression [ 16 ], and peritraumatic distress symptoms [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%